Effect of Lactobacillus plantarum L125 strain with probiotic potential on physicochemical, microbiological and sensorial characteristics of dry-fermented sausages. (January 2020) - Pavli, Foteini G.; Argyri, Anthoula A.; Chorianopoulos, Nikos G.; Nychas, George-John E.; Tassou, Chrysoula C.
Abstract: The performance of the Lactobacillus plantarum L125 strain with probiotic potential, previously isolated from a traditional Greek fermented sausage, was assessed as an adjunct culture for the production of dry-fermented pork sausages. The probiotic was added in the meat batter with the commercial starter cultures and the microbial populations were estimated during fermentation, ripening and storage at 4 and 12 °C, respectively. Physicochemical analyses (pH and a w ), sensory evaluation and Fourier Transform Infrared Spectroscopy (FTIR) were also performed, while the presence of L125 strain was monitored by Pulsed Field Gel Electrophoresis. Lactic acid bacteria (LAB) counts at the inoculation time were 8.21 and 6. 44 log CFU/g for the probiotic and control samples, respectively, while the L125 strain maintained high population levels (> 6 log CFU/g) during storage. At the end of the ripening, the products exhibited similar pH values of 4.46 and 4.42 and a w values of 0.87 and 0.85 for the control and probiotic case, respectively. FTIR spectroscopy application in combination with data analytics, resulted in the acceptable estimation of LAB population, but further studies are needed to improve the technique's performance. Overall, the Lb. plantarum L125 was found to possess desirable technological characteristics, indicating its effectiveness to be used in fermented sausage manufacturing. Highlights: Lb. plantarum L125 was assessed as adjunct probiotic culture in fermented sausages. Microbiological, physicochemical, sensory, molecular and FTIR analyses were performed. L125 was detected in high levels (> 6 log CFU/g) during storage. The new product showed sensorial properties similar to or better than the control. The microbial and sensory status of product were estimated through the FTIR-PLS models.